It's not you : identifying and healing from narcissistic people - Durvasula, Ramani (The Open Field/Penguin Life, 2024)
"Healing and thriving after or even during a narcissistic relationship can be challenging, but it is possible. It's Not You shows that the first step is to stop trying to change the narcissistic person, stop blaming yourself, and start giving yourself permission to foster your autonomy and sense of self outside of this relationship"--